Clinical Characteristics and Compliance of Diabetic Macular Edema Patients to Intravitreal Anti-VEGF Injection Loading Dose at Cipto Mangunkusumo Hospital: Oral Presentation - Observational Study - Resident - Kania, Theresia; Yudhanta, Anggun R (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesDiabetic retinopathy is the fifth most common cause of preventable blindness. In cases of diabeticmacular edema (DME), loading dose is a critical phase to achieve a stable concentration ofintravitreal vascular endothelial growth factor (VEGF) in order to prevent progressivity. This studyaims to determine the demographic and clinical characteristics, waiting time, compliance, as well asthe relationship between education, domicile and clinical outcomes to compliance during loadingdose in DME patients. MethodsIn this retrospective descriptive study, we reviewed medical records of DME patients who receivedanti-VEGF intravitreal injection between 1 January 2019 and 31 December 2020, while alsocomparing records in 2019 (pre-Covid-19) and 2020 (during Covid-19). ResultsThere were 160 patients (207 eyeballs) in 2019 and 83 patients (114 eyeballs) in 2020 who receivedloading dose with similar profiles of sex, age, education, initial visual acuity and central macularthickness (CMT). Median waiting times in 2019 and 2020 were 19 days and 23.5 days, respectively(p=0.016). Only 25 (30.5%) and 15 (35.7%) patients were punctual in 2019 and 2020, respectively.There was no significant relationship between education and domicile with compliance (p= 0.45, p=0.51). Furthermore, there were visual acuity improvements of -0.18 logMAR and -0.0 logMAR in thepunctual and unpunctual group, respectively, as well as CMT decrease of -181 ?m and -156 ?m,respectively. ConclusionMost patients who received loading dose were unpunctual. There was no significant relationshipbetween education and domicile with compliance. Furthermore, there were more significantimprovements in clinical outcomes among the punctual patients.